Developing and evaluating a health pack to support dog owners to manage the weight of their companion animals - Webb, Thomas L.; Molina, Jenifer; Sheridan, Libby; du Plessis, Hugues; Brown, Joanna; Abraham, Hannah; Morton, Oliver; McKay, Susan (Frontiers in Veterinary Science, 2025)
IntroductionObesity is a serious and prevalent problem in dogs. The causes are multifactorial, but owners play a key role and so this paper reports the development and evaluation of a health pack designed to help owners to manage the weight of their dogs.MethodThe pack was informed by previous research, behavior change theory (i.e., the COM-B model), and interviews with 12 veterinary professionals to identify challenges and potential solutions. Six workshops with a total of 28 dog owners provided feedback on the initial ideas. The pack included information on the importance of weight management, how to weigh and assess body condition score (BCS), a journal to track progress, an infographic illustrating the calorific value of treats, cards to help owners manage difficult situations, and a collar tag for the dog. The acceptability of the materials and potential outcomes were evaluated in a pre-registered pilot trial with a sample of 78 dog owners who were posted a health pack, 49 of whom completed a follow-up questionnaire.ResultsThe findings suggested that owners were willing to weigh their dog, found the pack acceptable, and there was preliminary evidence that the weight and BCS of dogs was lower at follow-up than at baseline.DiscussionThe findings illustrate the potential of a health pack for supporting dog owners and provide the basis for a larger RCT to formally evaluate effectiveness.